INTEGRASI TEKNOLOGI INFORMASI KOMUNIKASI DALAM PENDIDIKAN: POTENSI MANFAAT, MASYARAKAT BERBASIS PENGETAHUAN, PENDIDIKAN NILAI, STRATEGI IMPLEMENTASI DAN PENGEMBANGAN PROFESIONAL - Herry Fitriyadi (Faculty of Engineering, Universitas Negeri Yogyakarta, 2013)
ABSTRACTThe Integration of ICT in this life, nowadays,has given many changes including in the education field. The use of ICT offers many opportunities for better learning experience. It becomes a challenge to realize the integration of technology and learning process. The following conclusions had been reached from this paper: (1) some potential benefits of ICT for education were to enable the lifelong learning; to change the role of teachers and the role of students; to provide a public access for material content and interactive information through the network; to overcome the constraints of time and space in the learning environment; to reinforce the organization and learning management, and to create collaboration between teachers and students (2) realizing knowledge-based society, several actions need to be conducted, such as ensuring that everyone had ICT competencies and developed the other key competencies through ICT to participating in the community; setting the learning goals for the emancipation and empowerment as well as improving ICT literacy as part of the continous lifelong learning (3) the internalization process on ICT learning can be transformed by promoting as cultural activities in the school environment through the integration of educational values in the learning materials, thus, habituation, assignment, and role modelling being integral and holistic, which was continuously being part of learning, understanding, practicing in the daily life (4) implementation strategy and professional development in ICT field should refer to the teaching and learning activities. The indicators that should be developed were: accessibility indicator, output indicators and impact indicators. Directed and systematic policy can refer to the level of ICT-Based School, namely: Precursor, Basic, Intermediate, and Well-established where each level was determined from the factors of infrastructure, human resources, content, learning, as well as policy and program.Keywords: ICT integration, implementation strategy